THE COMPETITIVENESS OF SOYBEAN PRODUCTION IN BLITAR-EAST JAVA, INDONESIA - Arisudi, Moh. Azis; Gapor, Salfarina Abdul (Universitas Muhammdaiyah Surakarta, 2008)
In East Java Province, the government still provides subsidy to soybean production in the form of soft credit to production inputs. Since the government budget and subsidy have been limited, efficiency in production, marketing and trade become crucial issues. The conducted research will try to achieve some research objectives as follows: Analyzing soybean farmer income in the Blitar District at the different cropping system; Obtaining analysis on comparative advantage and competitive-ness of soybean by different cropping system; analyzing influences of social price changes to farmers income due to public investment; and analyzing government policy impact on farmers income due to market/actual price development. The research uses Policy Analysis Matrix to obtain competitiveness rate, efficiency and impact of government policy on soybean production under multi-cropping system and different ecological zones in the Blitar district.